VIEWING CONTRASTIVE RHETORIC FROM A POST MODERN PERSPECTIVE: FINDING AN IMPLICATION TO THE SECOND LANGUAGE WRITING PEDAGOGY - Susilo Susilo (Soegijapranata Catholic University, 2007)
The hybrid nature of culture that comes up as a result of postmodern world brings about considerable interaction, borrowing, and fusion between cultures and communicative genres. In such situation, there is erosion of national boundaries, greater multilingualism, and fluidity in identity; hence a